THE LOSS OF STATE-OWNED ENTERPRISE (BUMN) AS NOT STATE LOSS IN SEPARATION PRINCIPLE PERSPECTIVE - Siska Ambarwati; Yuliati Yuliati; Hanif Nur Widhiyanti (Jurnal Pembaharuan Hukum, 2022)
The study aims to analyze, first, the BUMN sub-holding loss as a state loss and secondly, the responsibility of the BUMN holding company for the BUMN sub-holding loss. There is a dualism in the conception of state assets that are separated from BUMN in Indonesian laws and regulations. The research methods was normative legal research with a statutory approach and a case approach. The shares of BUMN sub-holding don’t come from the state but come from the BUMN and also the public. The capital investment which it does by the BUMN holding company to the BUMN sub-holding doesn’t make the BUMN sub-holding become a BUMN. In the Group Company, the principle of a separate entity continues to apply which leads to the principle of limited liability holding as a subsidiary shareholder. However, if BUMN as the majority shareholder has the right to actively intervene and it is proven that there is control of the company, then the principle of piercing the corporate vision can be applied. So the BUMN holding company must be responsible for BUMN sub-holding because of the control carried out by these BUMN holding companies. The results show that the BUMN sub-holding loss isn’t state loss.